Transformasi Akuntansi Syariah di Era Digital: Peluang dan Tantangan bagi Lembaga Keuangan Islam - Mesya Nandawani Manik; Rayyan Firdaus (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Along with the development of technology in the digital era, Islamic accounting has increased from year to year. Life in accounting such as reading, recording, and calculating is now starting to be transferred to technology. This study was conducted to determine the impact of digitalization on Islamic accounting in Indonesia, as well as the opportunities and challenges for the Islamic accounting profession. Digital transformation includes the application of these innovations such as financial technology (fintech), blockchain, and artificial intelligence in the context of Islamic finance. This article discusses the opportunities and challenges faced by Islamic financial institutions in implementing Islamic accounting in the digital era. On the one hand, digitalization opens up opportunities to increase efficiency, accuracy, and transparency in Islamic financial reports, as well as expand public access to Islamic-based financial products. On the other hand, challenges related to the complexity of integrating digital systems that comply with Islamic principles, data security, and effective supervision are still important issues. The results of this study indicate that digitalization has a significant influence on the growth of Islamic-based accounting, especially in Indonesia.